The Learning Cycle 7-E Model Application Effect on Mathematics Critical Thinking Skills (MCTS) of Junior High School Students - Zubaidah Amir MZ; masrianti fadilah (Mathematics Research and Education Journal, 2022)
This study aimed to check the differences in MCTS between students using the 7-E Learning Cycle and students using the direct learning model. An experimental type was used with a quasi-experimental approach. The sampling technique used is purposive sampling. A normality test was carried out to see the study results. A homogeneity test was conducted using the sample's standard deviation and class average. A t-test was performed to determine the differences between the two classes. Results showed differences in MCTS between students learning the 7-E Learning Cycle model and direct learning with the t-count value of 4.83, the average value of the practical class is 88 .04. The average value of the control class is 71.32. The results of this study are one of the results that show that the MCTS of students can be improved with appropriate and supportive learning models.